Effects of the microcystin profile of a cyanobacterial bloom on growth and toxin accumulation in common carp Cyprinus carpio larvae - I. El Ghazali; S. Saqrane; A. P. Carvalho; Y. Ouahid; F. F. Del Campo; V. Vasconcelos; B. Oudra (Journal of Fish Biology, 2010)
A 12 day growth trial was conducted to compare the effect of the variation in microcystins (MC) composition of two bloom samples of Microcystis aeruginosa on the growth performance and microcystin accumulation in common carp Cyprinus carpio larvae. Two M. aeruginosa natural bloom samples with different MC profiles were collected and larvae were exposed to cyanobacterial cells through their diet. Three diets, a basal control diet and two diets prepared from the basal diet plus the same toxins content (60 ng MC g −1 diet) of each cyanobacterial bloom, were given at the same ration level to three groups of larvae during the experimental period. Larval mass and standard length from day 9 were significantly different between cyanobacterial treatments and in both cases lower than that of the control. The MC accumulation by larvae, inversely correlated with the growth performance, was also significantly different between cyanobacterial treatments (26·96 v . 17·32 ng g −1 at the end of the experimental period). These results indicate that MC variants profile may have effects on the toxin uptake and toxicity. To date, this is the first laboratory study to show that fish accumulate MC depending on the toxin profile of the cyanobacterial bloom.